Does routine pressure wire assessment influence management strategy at coronary angiography for diagnosis of chest pain?: the RIPCORD study. - Curzen, N; Rana, O; Nicholas, Z; Golledge, P; Zaman, A; Oldroyd, K; Hanratty, C; Banning, A; Wheatcroft, S; Hobson, A; Chitkara, K; Hildick-Smith, D; et al. (Lippincott Williams and Wilkins, 2014)
BACKGROUND: The use of coronary angiography (CA) for diagnosis and management of chest pain (CP) has several flaws. The assessment of coronary artery disease using fractional flow reserve (FFR) is a well-validated technique for describing lesion-level ischemia and improves clinical outcome in the context of percutaneous coronary intervention. The impact of routine FFR at the time of diagnostic CA on patient management has not been determined. METHODS AND RESULTS: Two hundred patients with stable CP underwent CA for clinical indications. The supervising cardiologist (S.C.) made a management plan based on CA (optimal medical therapy alone, percutaneous coronary intervention, coronary artery bypass grafting, or more information required) and also recorded which stenoses were significant. An interventional cardiologist then measured FFR in all patent coronary arteries of stentable diameter (≥2.25 mm). S.C. was then asked to make a second management plan when FFR results were disclosed. Overall, after disclosure of FFR data, management plan based on CA alone was changed in 26% of patients, and the number and localization of functional stenoses changed in 32%. Specifically, of 72 cases in which optimal medical therapy was recommended after CA, 9 (13%) were actually referred for revascularization with FFR data. By contrast, of 89 cases in whom management plan was optimal medical therapy based on FFR, revascularization would have been recommended in 25 (28%) based on CA. CONCLUSIONS: Routine measurement of FFR at CA has important influence both on which coronary arteries have significant stenoses and on patient management. These findings could have important implications for clinical practice. CLINICAL TRIAL REGISTRATION URL: http://www.clinicaltrial.gov. Unique identifier: NCT01070771.